2007
DOI: 10.1002/jbm.b.30910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of load and indicator type upon occlusal contact markings

Abstract: Observation of the marks recorded with the thicker occlusal indicator demonstrated both a greater number marks and a larger size to the marks when compared to the thinner Accufilm, p < or = 0.02-0.0001. However, there was no significant increase in the number or size of the marks with an increased load for either material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 49 publications
(80 reference statements)
3
54
1
4
Order By: Relevance
“…Another study, conducted in 2008, comparing the effect of articulating paper thickness (25 lm or 60 lm) on contact marking at pressures ranging from 100 N to 200 N, found there was no significant increase in the number or size of the marks with increased pressure for either thickness of paper. As expected, the thicker paper created more marks, which were generally of larger size than with thin paper 38 .…”
Section: Computerized Occlusal Analysis In Dentofacial Orthopedics: Isupporting
confidence: 74%
See 1 more Smart Citation
“…Another study, conducted in 2008, comparing the effect of articulating paper thickness (25 lm or 60 lm) on contact marking at pressures ranging from 100 N to 200 N, found there was no significant increase in the number or size of the marks with increased pressure for either thickness of paper. As expected, the thicker paper created more marks, which were generally of larger size than with thin paper 38 .…”
Section: Computerized Occlusal Analysis In Dentofacial Orthopedics: Isupporting
confidence: 74%
“…Variations in articulating paper marking may also arise from differences in paper thickness, the extent to which it is impregnated with saliva, and the force of the patient's bite. Because of these types of variation, many researchers have been able to demonstrate that contact profiles determined using articulating paper are not reproducible, even when made under apparently identical conditions 9,20,31,38,39 .…”
Section: -3 -A Comparative Analysis Between Digitized Occlusal Force mentioning
confidence: 99%
“…When ink-based or dye-containing articulating papers are chosen, biting on them is required in order to visually disclose tooth contacts; this task involves the activation of the masticatory system and its related musculature. Commercially available paper indicators differ in material composition, thickness, mechanical ductility and tensile strength; previous studies have investigated the physical features of these media (Halperin et al , 1982), or the influence of specific properties on the appearance of occlusal markings (Saad et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Schelb et al [3] found that paper mark size is proportional to paper thickness, not to the applied occlusal load. Similarly, Saad et al [4] used articulated epoxy casts to crush articulating paper at three distinct loads (50 N, 100 N, and 150 N), where the resultant paper mark sizes did not appreciably increase, despite the load doubling and tripling. The authors found that as the load doubled and tripled, the paper mark sizes decreased, instead of going up in size.…”
Section: The Dogma Of Occlusal Paradigms: What Do We Really Have Figumentioning
confidence: 99%